Chemical reactivity of Bushveld Igneous Complex mine residues for mineral beneficiation - Van der Merwe, E.M. (Elizabet Margaretha) (University of Pretoria, 2024)
Thesis (PhD (Chemistry))--University of Pretoria, 2024.